Freeze-like responses to pain in humans and its modulation by social context - Kai Karos; Ann Meulders; Tine Leyssen; Johan W. Vlaeyen (PeerJ, 2020)
Background Maladaptive defensive responses such as excessive avoidance behavior have received increasing attention as a main mechanism for the development and maintenance of chronic pain complaints. However, another defensive response which is commonly studied in animals as a proxy for fear is freezing behavior. No research to date has investigated human freezing behavior in the context of pain. In addition, there is an increasing realization that social context can affect pain-relevant processes such as pain experience and pain behavior but less is known about the effects of social context on defensive responses to pain. Hence, this study investigated freezing behavior and facial pain expression in the context of pain, and their modulation by social context. Methods Healthy, pain-free participants (N = 39) stood on a stabilometric force platform in a threatening or safe social context, which was manipulated using angry or happy facial stimuli. In some trials, an auditory cue (conditioned stimulus; CS) predicted the occurrence of painful electrocutaneous stimulus (unconditioned stimulus; pain-US). We assessed body sway (an index of freezing), heart rate, facial pain expression, self-reported pain intensity, unpleasantness, and pain-US expectancy during the CS and the context alone (no CS). Results The results were mixed. Neither the anticipation of pain, nor social context affected body sway. Heart rate and painful facial expression were reduced in the threatening social context at high anxiety levels. A threatening social context also elicited higher pain-US expectancy ratings. In sum, a threatening social context increases the expectation of pain, but reduces the facial expression of pain and lowers heart rate in highly anxious individuals.